BUSINESS REGULATIONS: CONSTRAIN OR SAFEGUARD BUSINESS ACTIVITY? (THE IMPORTANCE OF REGULATORY IMPACT ASSESSMENT) - Dorina Koci (Janku) (European Scientific Journal, ESJ, 2013)
Poor quality of laws and regulations can seriously hamper economic growth and sustainable development. Regulatory costs represent significant obstacles to private sector investment, whereas, an effective regulatory environment improves trade performance. Rules and regulations are under the direct control of policy-makers and policy makers intending to change the experience and behavior of businesses will often start by changing rules and regulations that affect them. Good business regulations enable the private sector to prosper and help businesses to expand their transaction network.In this context, the regulations seem to safeguard economic activity and facilitate business operations. By other side, if regulations are poorly designed, they can become obstacles to doing business. Business regulations are part of institutional constraints.The main purpose of this paper is, to offer a comparative analysis of reforms undertaken by different European countries (especially Balkan countries), through an interpreter and descriptive analysis using the data set provided by Doing Business Report (2013) in order to evaluate the position of Albania towards its neighbors. The comparison will cover two sides: what has been done (reforms making it easier to do business) and what must be done in the future. Subsequently, the importance of regulatory reforms describing the main benefits of a reform impact assessment (RIA) process will be in focus of the paper. It is important for governments not only to implement a policy but also to understand and evaluate how well this policy will work.